1996
DOI: 10.1007/bf01411059
|View full text |Cite
|
Sign up to set email alerts
|

Chronic precentral stimulation in trigeminal neuropathic pain

Abstract: The results of Deep Brain Stimulation in deafferentation pain syndromes, in particular in thalamic pain, indicate that excellent long-term pain relief can hardly ever be achieved. We report 7 cases using Motor-Cortex-Stimulation for treating severe trigeminal neuropathic pain syndromes, i.e., dysaesthesia, anaesthesia dolorosa and postherpetic neuralgia. The first implantation of the stimulation device for precentral cerebral stimulation was performed in June 1993, the last in September 1995. In all but one ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
93
1
4

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(100 citation statements)
references
References 19 publications
2
93
1
4
Order By: Relevance
“…13 Other effects directly attributed to MCS include epileptic and focal seizures, aphasia and dysphasia, upperextremity fatigue, burning sensations in the area of stimulation, and the presence of left-sided supernumerary arm in the affected area. 3,13,15,18,19 No seizures or other complications have been reported as a result of long-term stimulation delivered at optimum settings. …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…13 Other effects directly attributed to MCS include epileptic and focal seizures, aphasia and dysphasia, upperextremity fatigue, burning sensations in the area of stimulation, and the presence of left-sided supernumerary arm in the affected area. 3,13,15,18,19 No seizures or other complications have been reported as a result of long-term stimulation delivered at optimum settings. …”
mentioning
confidence: 99%
“…Variable response rates related to various implantation techniques have been reported in patients with central and peripheral neuropathic pain. [1][2][3][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] Table 1 provides a summary of these reported cases and series, as well as details of the optimum stimulator settings and the overall long-term response to MCS. The evidence suggests that a positive response is achieved in 44 to 100% of MCS-treated patients.…”
mentioning
confidence: 99%
“…Tricyclic antidepressants, gabapentin, intrathecally local anaesthetics and corticosteroids are the medical treatments used. In the surgical approach, peripheral neurectomy, percutaneous gangliolysis, motor cortex stimulation, stereotactic trigeminal nucleotomy, stimulation of the Gasserian ganglion and trigeminal rootlets are used for trigeminal neuropathic pain (3,12,13,16,18,20,21,26,27). However, we performed CT-guided trigeminal tractotomy for the treatment of this special case.…”
Section: Discussionmentioning
confidence: 99%
“…The location of the burr hole was determined by standard anatomical landmarks and skin-surface SSEPs, and the electrode was placed through the burr hole over the approximate location of the motor cortex. 5,15 In later reports by Ebel, et al, 2 and Peyron, et al, 9 the authors suggested that a craniotomy should be used rather than a burr hole, allowing for more extensive mapping of the rolandic region. Further refinement of the technique with the introduction of anatomical image guidance, as described by Nguyen and colleagues, 7,8 has been associated with improved long-term results.…”
Section: Discussionmentioning
confidence: 99%